Analysis of Swelling Behavior of Fakfak Clay Soils Stabilized with Lime: Analisis Perilaku Kembang Susut Tanah Lempung Fakfak yang Distabilisasi dengan Kapur - Nurul Muhlisah; Jusmawandi; Risma Niswati Tarman (PUBLIKASI RISET ORIENTASI TEKNIK SIPIL (PROTEKSI), 2025)
Clay soils often exhibit problematic characteristics. Expansive clay, which has swelling and shrinkage properties that are influenced by its moisture content. The study analyze the effect of lime mixing on the swelling and shrinkage behavior of soil. The method used involves mixing Fakfak clay with lime in proportions of 0%, 2%, 4%, 6%, and 8%, with a curing period of 3 days. The original soil used is classified as OH or A-7-5, with an average moisture content of 50.51%, a bulk density of 0.612 g/cm³, a specific gravity of 2.3, a liquid limit of 61.59%, a plastic limit of 48.86%, and a shrinkage limit of 32.94%, with a plasticity index of 12.73%, classified as medium plasticity and cohesive. The results showed that soil plasticity decreased with increasing lime content, with the lowest value found at 8% lime (1.04%). The largest shrinkage limit was found in the 2% lime mixture (33.27%), while the smallest was in the 8% lime mixture (28.77%). The conclusion lime mixing is effective in improving the soil's condition, with the 8% lime mixture demonstrating a stable composition with respect to the swelling behavior, compared to both the original soil and other lime mixtures.